How to Speed up Arabic Literacy for Lower-Income Students? : Some Insights from Cognitive Neuroscience - Abadzi, Helen (World Bank, Washington, DC, 2017)
Students in low-income countries often have trouble learning to read; 80-90 percent of second and third graders in some countries cannot even read a single word and may know few if any letters (RTI 2009, 2010, 2011a, 2011b). The reasons are linked to limited instructional time, textbooks or parental help, potentially poor nutrition, or complex teaching methods that originated in high-income countries. Despite relative affluence, the academic performance in the Arab world has been a problem, with countries scoring on international tests much lower than expected based on per capita income level. Similarly Early Grade Reading Assessments (EGRA) in various countries has shown lower reading speeds than one would expect. In Pakistan and Afghanistan, which use the Arabic script, the issues are similar. The interaction of the perceptual and linguistic complexities turns Arabic reading into a complex multistage exercise. A reader of the Arabic script must: (a) decipher the text, (b) predict the vowels and keep multiple alternative words in working memory to test and decide on meaning, and (c) make linguistic sense in the case of Arabic. This process means that readers need to identify words faster than in other scripts in order to make sense of the text, but in fact they identify them more slowly. Not surprisingly, some studies suggest that the Arabic script may be read more slowly than visually simpler scripts or linear scripts. Education for All implies that nearly all students must somehow learn fluent reading very quickly when they start school in order to then progress to higher level topics. This must be achievable in all the languages and scripts used in low-income countries. By focusing on these lower-level variables this is doable.